2011
DOI: 10.1111/j.1708-8208.2011.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective 10‐Year Cohort Study Based on a Randomized, Controlled Trial (RCT) on Implant‐Supported Full‐Arch Maxillary Prostheses. Part II: Prosthetic Outcomes and Maintenance

Abstract: Fracture or wear of the reconstruction materials were considered predictable risks when using resin-based suprastructure materials. Status of opposing dentition and length of cantilevers did not confer additional risk. The use of a lingual gold onlay indicated prevention of resin-related complications. Future research should focus on the suprastructure materials to predict better overall treatment results of implant-supported full-arch bridges in the edentulous maxilla.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 24 publications
(46 reference statements)
6
53
0
7
Order By: Relevance
“…The CPGs are presented in Table 3 for tooth-borne restorations [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and Table 4 for implant-borne restorations. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] For tooth-borne restorations, the professional maintenance and at-home maintenance CPGs were subdivided for removable and fixed restorations. For implant-borne restorations, the professional maintenance CPGs were sub-divided for removable and fixed restorations and further divided into biological maintenance and mechanical maintenance for each type of restoration.…”
Section: Resultsmentioning
confidence: 99%
“…The CPGs are presented in Table 3 for tooth-borne restorations [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and Table 4 for implant-borne restorations. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] For tooth-borne restorations, the professional maintenance and at-home maintenance CPGs were subdivided for removable and fixed restorations. For implant-borne restorations, the professional maintenance CPGs were sub-divided for removable and fixed restorations and further divided into biological maintenance and mechanical maintenance for each type of restoration.…”
Section: Resultsmentioning
confidence: 99%
“…26 Differences in terms of complications and failures of final full-arch implant rehabilitations made in resin versus those made in zirconia were not detected during the observation period.…”
Section: Discussionmentioning
confidence: 90%
“…26,57 In particular, the most common prosthesis-related technical complication reported with implantsupported complete dental prostheses was chipping or fracture of the veneering material (33.3% at 5 years) as a result of fatigue and stress. In a prospective study regarding a clinical test over a period of 36 months, Duncan et al 54 reported that 68% of patients provided with fixed detachable prostheses had complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations